2021
DOI: 10.3390/nano11041003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Morphologically Controlled Hematite Nanoparticles on the Properties of Fly Ash Blended Cement

Abstract: Several types of hematite nanoparticles (α-Fe2O3) have been investigated for their effects on the structure and properties of fly ash (FA) blended cement. All synthesized nanoparticles were found to be of spherical shape, but of different particle sizes ranging from 10 to 195 nm depending on the surfactant used in their preparation. The cement hydration with time showed 1.0% α-Fe2O3 nanoparticles are effective accelerators for FA blended cement. Moreover, adding α-Fe2O3 nanoparticles in FA blended cement enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
0
0
Order By: Relevance
“…Zhang et al [59] and Bhenia et al [60] also reported similar results with SiO 2 additives. Additionally, Kongsat et al [61] obtained similar results with Fe 2 O 3 doping. It is well known that the pozzolanic activity of SiO 2 accelerates hydration reactions and leads to a decrease in setting times [62,63].…”
Section: Mortar Strength Setting Times and Durability Studiesmentioning
confidence: 64%
“…Zhang et al [59] and Bhenia et al [60] also reported similar results with SiO 2 additives. Additionally, Kongsat et al [61] obtained similar results with Fe 2 O 3 doping. It is well known that the pozzolanic activity of SiO 2 accelerates hydration reactions and leads to a decrease in setting times [62,63].…”
Section: Mortar Strength Setting Times and Durability Studiesmentioning
confidence: 64%
“…By acting as a reinforcing load, these particles improve compressive strength. 35 This may be an indication that the iron(III) from hematite is unlikely to be part of the geopolymerisation process. Zhu et al reported that the presence of iron(III) binds mainly to hydroxyl groups, which increases the number of nucleation sites and thus the geopolymerisation process, and hence the compressive strength.…”
Section: Compressive Strengthsmentioning
confidence: 99%